2018
DOI: 10.18633/biotecnia.v20i3.722
|View full text |Cite
|
Sign up to set email alerts
|

LIBERACIÓN DE COMPUESTOS FENÓLICOS LIGADOS EN EL GARBANZO (Cicer arietinum L.) UTILIZANDO MICROBIOTA HUMANA INTESTINAL

Abstract: El garbanzo es una legumbre que además de aportar nutrientes para la salud, contiene una serie de compuestos bioactivos, principalmente compuestos fenólicos considerados altamente antioxidantes. Por lo tanto, puede prevenir enfermedades generalmente crónico-degenerativas. El problema con estos compuestos es que alrededor del 70 al 90 % se encuentran ligados a la matriz alimentaria a través de enlaces covalentes; para que puedan pasar a torrente sanguíneo y ejercer su actividad biológica (biodisponibilidad) tie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…Therefore, these compounds must pass to the large intestine, where they will be metabolized by the intestinal microbiota producing lower molecular weight phenols with higher absorption. Consequently, these compounds’ antioxidant capacity will increase because the functional groups of phenolic compounds will be more exposed [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, these compounds must pass to the large intestine, where they will be metabolized by the intestinal microbiota producing lower molecular weight phenols with higher absorption. Consequently, these compounds’ antioxidant capacity will increase because the functional groups of phenolic compounds will be more exposed [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…One characteristic that gives the antioxidant capacity is the hydroxyl groups, which are attached to a benzene ring, as in the case of polyphenols, present the possibility that the free radical interacts with ring electrons, which gives them special characteristics with respect to other alcohols. Therefore, it will depend on its structure, where it has been found that the greater the hydroxylation, the higher the antioxidant capacity [ 2 , 61 ]. Besides the hydroxyl groups, other factors make a molecular antioxidant, such as double bonds in the structure, hindrance steric, and the hydroxyl group’s position.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenolic compounds are the majority of secondary metabolites in safflower. The function of these molecules is to provide better development and growth and, in turn, be a defense mechanism (Perez-Perez et al, 2018). In addition, the importance of phenolic compounds is that they have a protective effect on the organism, neutralizing free radicals, and causative chronic degenerative diseases (Tapia-Hernández et al, 2018).…”
mentioning
confidence: 99%